HUBUNGAN STATUS GIZI REMAJA DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Sri Handayani; Yopi Suryatim Pratiwi; Dian Soekmawaty Riezqy Ariendha (LPPM Universitas Abdurrab, 2023)
Adolescent girls who experience anemia are still high in Indonesia, namely by 23%, mainly due to iron deficiency. This study aims to analyze the nutritional status of adolescents with the incidence of anemia in female adolescents. The design in this study was a cross sectional study. The sample in this study were all students of the Midwifery Study Program Undergraduate Program and Midwifery Study Program Diploma Three STIKES YARSI Mataram who were included in the group of older adolescents, namely 17-20 years of age as many as 80 respondents. Nutritional status was determined based on Body Mass Index (BMI), while anemia status was determined based on hemoglobin levels as measured using the Easy Touch brand hemoglobin strip. Bivariate analysis was tested with Pearson Chi-square. The results showed that anemia was not related to the nutritional status of young women with a value of p=0.475 (p>0.005). This is because anemia has many risk factors, including length of menstruation, iron intake, and consuming iron absorption inhibitors. Therefore, it is recommended for young women to consume iron-rich foods and iron tablets.